What is the fittest criterion for giving chemotherapy for an elderly patient diagnosed with follicular lymphoma? - Turgay ULAS Mehmet Sinan DAL; Ozan SALIM (Archive of Gerontology and Geriatrics Research - Peertechz Publications, 2020)
An 85-year-old British man admitted to our department in July 2018 with enlarged lumps in cervical, axillary and inguinal sites. He was diagnosed with Follicular lymphoma (Stage 3 Grade 3A). In his past history, September 2017, he had undergone percutaneous coronary stent intervention to the left anterior descending coronary artery. Treatment for lymphoma was needed due to the high tumor burden.